Answer:
(0,-2), (5,0) and (10,2).
Step-by-step explanation:
Given equation is
.
Now we need to find 3 pairs of solutions in (x,y) form for the given equation.
As
is a linear equation so we are free to pick any number for x like x=0, 5, 10
Plug x=0 into
, we get:
![2(0)-5y=10](https://tex.z-dn.net/?f=2%280%29-5y%3D10)
![0-5y=10](https://tex.z-dn.net/?f=0-5y%3D10)
![-5y=10](https://tex.z-dn.net/?f=-5y%3D10)
![y=\frac{10}{-5}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B10%7D%7B-5%7D)
![y=-2](https://tex.z-dn.net/?f=y%3D-2)
Hence first solution is (0,-2)
We can repeat same process with x=5 and 10 to get the other solutions.
Hence final answer is (0,-2), (5,0) and (10,2).
Answer:
(Choice B)
Step-by-step explanation:
Solve the following expression:
![9(5x - 5) + 7x](https://tex.z-dn.net/?f=9%285x%20-%205%29%20%2B%207x)
-Use <u>Distributive Property</u>:
![9(5x - 5) + 7x](https://tex.z-dn.net/?f=9%285x%20-%205%29%20%2B%207x)
![45x - 45 + 7x](https://tex.z-dn.net/?f=45x%20-%2045%20%2B%207x)
-Combine like terms:
![45x - 45 + 7x](https://tex.z-dn.net/?f=45x%20-%2045%20%2B%207x)
![\boxed {52x - 45}](https://tex.z-dn.net/?f=%5Cboxed%20%7B52x%20-%2045%7D)
Answer: 1
y=1x-3
m=-3/-3=-1/-1=1
6x² + 2x - 20 = 0
3(2x² + x - 10) = 0
3[(2x² - 4x + 5x - 10)] = 0
3[2x(x - 2) + 5(x - 2)] = 0
3(2x + 5)(x - 2) = 0
3=0, 2x + 5 = 0, x - 2 = 0 (Note: 3=0 is false so disregard that equation)
x =
, x = 2
Answer: x = {
, 2}